Semantic Shifts in Political Discourse: A Study of Language Manipulation - meisuri meisuri; Hassan Al-Haddad (Journal of Humanities Research Sustainability, 2025)
Background. Semantic shifts in political discourse are a phenomenon that is increasingly occurring in modern political communication. Language manipulation is used by political actors and the media to shape public opinion, reframe an issue, and create new meanings that suit certain political interests. This strategy not only has an impact on how the public understands policies, but also on the political dynamics that develop in them. Purpose. This study aims to analyze how semantic shifts are used in political discourse as well as how changes in the meaning of words can affect public perception. The study also examines how politicians and the media utilize linguistic strategies to manipulate political discourse and shape certain narratives on a variety of evolving political issues. Method. This study uses critical discourse analysis and semantic linguistic analysis methods to examine 78 political documents, including politicians' speeches, debate transcripts, media news, and policy documents. The data was analyzed with a thematic approach to identify patterns of semantic shifts that emerged in political communication. Results. The analysis showed that political metaphors were a key tool in semantic shifts, with a percentage of 32% of the total documents analyzed. Framing strategies and diction manipulation are also used to build political narratives that benefit certain actors. Shifts in the meaning of words are often used to lead public opinion without them realizing it, thus creating a bias in the understanding of political issues. Conclusion. Semantic shifts are not just linguistic changes, but are political communication strategies that have a wide impact on public opinion and political policy. Awareness of this phenomenon can help the public be more critical in understanding the developing political discourse. This research contributes to deepening the understanding of how language is used as a tool of power in politics and how political literacy can be developed to deal with semantic manipulation in political communication.